Technology Acceptance Model (TAM) Untuk Mengukur Minat Adopsi Green Transportation Sepeda Motor Listrik di Kalimantan Barat - Asri Hidayati; Adiyath Randy Yudimamase; Henrian Stiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Climate change and air pollution are necessitating a transition towards sustainable transportation. However, the adoption rate of electric motorcycles in West Kalimantan remains low. This study aims to analyze the factors shaping the intention to adopt electric motorcycles in this region using an extended Technology Acceptance Model (TAM) framework. A quantitative method was employed, involving a survey of 200 respondents selected through purposive sampling, with the data analyzed using Structural Equation Modeling (SEM). The results indicate that perceived usefulness and perceived ease of use have a positive and significant influence on adoption intention. Notably, perceived ease of use emerged as the most dominant determinant, not only directly impacting intention but also indirectly influencing it through perceived usefulness. Among the external variables, compatibility was found to enhance perceived usefulness, while enjoyment positively affected perceived ease of use. Conversely, resource availability did not significantly shape initial perceptions. The implications of these findings suggest that stakeholders should prioritize strategic communication that highlights the ease of use, enjoyable riding experience, and functional benefits of electric motorcycles. These efforts should be supported by policies aimed at accelerating infrastructure development and providing incentives to encourage broader adoption.